Polar coordinates in taekwondo - Menescardi, C.; Estevan, I.; Falcó, C. (Revista de Artes Marciales Asiaticas, 2016)
In observational methodology, inter-relational behaviors are relevant for coaches and athletes to know which behaviors are dependent or inexistent while others occur. Polar coordinates analysis allows researchers to provide an inter-relational map of behaviors (from focal to conditioned ones) represented by vectors (Anguera & Hernandez-Mendo, 2014). To date, there is only one study in taekwondo that applied this statistical technique (Lopez-Lopez, Menescardi, Estevan, Falco, & Hernandez-Mendo, 2015). This study showed a relationship of anticipatory counterattack actions with effective attacks performed by using kicks to the chest (Lopez-Lopez, et al., 2015). The revision of the current literature suggested a lack of behavioral patterns studies in combat sports. Thus, the purpose of this study is to analyze the relationships between tactical actions (direct attack [DA], indirect attack [IA], anticipatory counterattack [AC], simultaneous counterattack [SC], and posterior counterattack [PC]) of taekwondo to extract behavioral patterns which could be used to train the tactics based on empirical evidences.